A Design Of Prepaid Electricity Credit Recharge System Based On Dual Tone Multiple Frequency - Habib Syahputra Banurea; Beni Satria; Solly Aryza (Jurnal Scientia, 2024)
In an effort to improve the efficiency and ease of prepaid electricity top-up, Dual Tone Multiple Frequency (DTMF) technology offers an innovative solution that allows users to top up electricity via telephone. This study aims to design and implement a prepaid electricity top-up system that uses DTMF technology as an input method. The research methodology includes hardware and software design consisting of several main components, namely a DTMF module, microcontroller, and communication module. The DTMF module is used to detect and convert dual tone signals from the telephone into digital data that can be processed by the microcontroller. The microcontroller then processes this data to control the prepaid electricity meter top-up process. The system development stage begins with the selection and configuration of the appropriate DTMF module, followed by microcontroller programming to identify the DTMF code sent by the user. The system also includes a verification mechanism to ensure that the code entered is valid and secure. After verification, the microcontroller sends a command to the prepaid electricity meter to top up the credit according to the amount entered. The test results show that the DTMF-based prepaid electricity top-up system functions well, is able to recognize DTMF codes with high accuracy, and performs top-ups efficiently. This system offers ease of use for prepaid electricity customers, eliminates the need to go to a physical credit sales location, and allows top-ups from anywhere using a telephone. The conclusion of this study is that the DTMF-based prepaid electricity top-up system is a reliable and effective solution to improve convenience and efficiency for prepaid electricity users. Further implementation can be focused on improving security and integration with digital payment systems to provide a more comprehensive solution.